The Civil Rights Movement and Its Impact on Black Minority and Obama’s Political Career - Laggoun ,Mohamed Bachir; kaid ,Nassima (Faculty of Letters and Foreign Languages Department of English, 2019)
The dissertation’s objectives are to examine and treat a specific era in the history of the United States of America, which it had witnessed and suffered from race issues. Also, this work is going to shed the light on one of the epic social and political event, that it took a place in the American society, which is the civil rights movement. This peaceful manifestation brought radical changes to African -Americans and the constitution by neglecting the injustice and maltreatment toward them. The impact of civil rights movement was the start to pave the way for many black leaders in order to achieve their goals; including Obama as the first black senate and from there to the presidency of the United States of America. Thanks to the civil rights movement, Obama was elected for two terms as the president of the United States and the African American minority is being treated equally